PENGARUH PENGETAHUAN, PENGALAMAN, KOMPLEKSITAS TUGAS DAN PROFESIONALISME TERHADAP KUALITAS AUDIT JUDGMENT PADA KANTOR AKUNTAN PUBLIK DI SURABAYA - Dewi Sutjahyani (Universitas Muhammadiyah Jember, 2020)
Public Accountant Office is a business entity that has obtained permission from the Minister of Finance as a container for public accountants to give his services. Given the increasing importance of reliable financial statements, the company requires an independent auditor to audit its financial statements. Financial statements that have been audited by an independent party also give the company the opportunity to go public.The purpose of research is to be achieved according to the formulation of problems that have been shown above to know, analyzing the factors that affect the audit of Judgment in Public Accountant Office in Surabaya. The research took 5 Public Accountant Office and the respondents numbered 31 respondents from a total of 5 Public Accountant Office in Surabaya. In this research secondary data is a questionnaire, secondary data used 31 questionnaires. The type of research to be used is using quantitative research methods by method. The analytical technique used is the analysis used by the analysis method of Partial Least Squares (PLS). Partial Least Squares (PLS) One of the software used to run the analysis PLS is SmartPLS. The hypothesis testing formulated in this study is using SmartPLS version 3.2.8 for Windows software Help. The tests conducted in this study consisted of an evaluation of the outer model (measurement model) and an evaluation of inner models (structural models).In the findings of the analysis using the evaluation of the outer model (measurement model) and evaluation of inner models (structural models) that simultaneously answered the hypothesis by concluding that, the knowledge variables (X1), Experience (X2), the complexity of the task ( X3) professionalism (X4) positively affects the audit judgment (Y), with a statistical value of T 1.709 for (X1); 1.593, to (X2); 0.388 for (X3); and 1.261 for (X4). While the original value of the sample, namely 0.326 for (X1); 0, 355for (X2); 0.062 for (X3); 0, 259 (X4) which means positive effect on the audit quality Judgment (Y).